Analisis Struktur Dimensi Kualitas Layanan Berbasis Pendekatan Faktor Analysis pada Sektor UMKM - Elsa Agustika Lubis; Elsi Agustina Lubis; Heri Hayanti; Putri Saadah; Selvia Indriani; Sunita Dasman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to identify the dimensional structure of service quality perceived by customers of Richeese Factory in the Cikarang area using Factor Analysis. The research employed a quantitative approach involving 100 respondents selected through a purposive sampling technique. Data were collected using a questionnaire comprising indicators of service environment quality, service effectiveness, service responsiveness, service credibility, and customer orientation. The data were then analyzed using IBM SPSS Statistics. The results indicate that the research instrument was reliable, with a Cronbach's Alpha value of 0.889, and suitable for factor analysis, as demonstrated by a Kaiser-Meyer-Olkin (KMO) value of 0.930 and a Bartlett's Test of Sphericity significance value of 0.000. The factor analysis extracted one principal factor with an eigenvalue of 7.244, explaining 48.290% of the total variance. All indicators exhibited factor loadings exceeding 0.50, indicating that they were appropriate to be retained in the research model. Among these, service credibility showed the highest contribution, with a factor loading of 0.776. The findings suggest that service quality at Richeese Factory Cikarang is perceived as a unidimensional construct, with service credibility serving as the primary factor shaping customers' perceptions of the overall service quality.